A retrospective study on newly diagnosed Hansen’s disease and its spectrum in a tertiary care hospital - Nageswaramma, Siddabathuni; Priyakumar Talamala, Sampath; S. P., Swathiga; Talluru , Vani (International Journal Of Community Medicine And Public Health, 2023)
Background: Leprosy, a well known ancient disease caused by the pathogen Mycobacterium leprae. Leprosy became curable with the introduction of multi drug therapy (MDT). But the burden of the disease still continues to make an impact in the present society. India is one of the major contributors to the global leprosy case load even after elimination. The main aim of this study was to assess the clinical pattern of newly diagnosed leprosy patients and to emphasize the need of timely intervention. Methods: This was a hospital based retrospective observational study. The medical records of all the newly diagnosed leprosy patients during the period of January 2022 to December 2022 were collected and various clinical and demographic factors were analyzed. Results: Total 139 newly diagnosed leprosy cases were reported. The most common age group affected was 45-60 years. Males were predominantly affected than females. 128 cases were multibacillary leprosy and 11 were paucibacillary. Borderline tuberculoid (48.2%) was the most common spectrum noted. About 19.4% patients presented with lepra reactions and 25.17% patients presented with deformities. Conclusions: Newly diagnosed leprosy cases show that leprosy is active in the society. Active case detection by household contact survey and timely referral &treatment initiation and follow up by the field staff of health facility will prevent disability and stigma.